2013
DOI: 10.1371/journal.pone.0075797
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Analysis of Nectar Pseudomonads Reveals High Genetic Diversity and Contrasting Recombination Patterns

Abstract: The genetic and evolutionary relationships among floral nectar-dwelling Pseudomonas ‘sensu stricto’ isolates associated to South African and Mediterranean plants were investigated by multilocus sequence analysis (MLSA) of four core housekeeping genes (rrs, gyrB, rpoB and rpoD). A total of 35 different sequence types were found for the 38 nectar bacterial isolates characterised. Phylogenetic analyses resulted in the identification of three main clades [nectar groups (NGs) 1, 2 and 3] of nectar pseudomonads, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 94 publications
0
34
0
Order By: Relevance
“…Bootscan, Maxchi, LARD recombination events detected by only half of the nine methods in RDP4 were considered significant (25,26), and the results obtained by three programs, PHI test, Recco, and RDP4, were not consistent, we concluded that only limited HR occurred in sigB of Listeria sensu stricto.…”
Section: Resultsmentioning
confidence: 83%
“…Bootscan, Maxchi, LARD recombination events detected by only half of the nine methods in RDP4 were considered significant (25,26), and the results obtained by three programs, PHI test, Recco, and RDP4, were not consistent, we concluded that only limited HR occurred in sigB of Listeria sensu stricto.…”
Section: Resultsmentioning
confidence: 83%
“…We included only those recombination events that are supported by at least three out of the nine methods in RDP to avoid dependence on a single methodology (RDP, BOOTSCAN, GENE-CONV, MAXCHI, CHIMAERA, SISCAN, PhylPro, LARD and 3Seq). Previous recombination studies using RDP have used the 3/9 criterion, with the expectation that true recombination events will likely be detected using different approaches (Bilhère et al, 2009;Cadillo-Quiroz et al, 2012;Alvarez-Pérez et al, 2013). The strength of RDP is its implementation of a variety of detection approaches to both identify and characterize recombination events, such as phylogenetic conflicts clustering of nucleotide substitutions and fitting of substitutions to an expected statistical distribution.…”
Section: Recombination Analysesmentioning
confidence: 99%
“…In general, the several housekeeping genes are widely applied in MLSA schemes, such as acsA , gyrB , mutL , rpoD , etc [22][25], because they encode core metabolic enzymes and own by all members of the organisms. Furthermore, the concatenated housekeeping genes could overcome conflicting signals from horizontal gene transfer and recombination.…”
Section: Introductionmentioning
confidence: 99%